Durian Seed Flour (Durio zibethinus Murr) as an Alternative Medium for Fungal Growth - Afriani, Tika; Rahmi, Azimatur; Ramadhani, Putri Agiel; Rahmadaniah, Rahmadaniah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
This study aimed to evaluate the potential of durian seed flour (Durio zibethinus Murr) as an alternative medium for the growth of Candida albicans and Aspergillus niger. The bleaching process utilized sodium metabisulfite at varying concentrations (600 ppm, 800 ppm, 1000 ppm) and immersion durations (15, 20, 25 minutes). The bleached samples were dried at 70â„ƒ for 3 hours. Durian seed flour media were formulated into three variants and compared with Potato Dextrose Agar (PDA) as the control medium. The activity test for Candida albicans used the pour plate method with incubation for 48 hours at 37â„ƒ, while Aspergillus niger was tested using the agar block method and incubated for 72 hours under the same conditions. Immersion duration significantly affected the flour's color, with longer durations producing whiter flour. Higher drying temperatures enhanced water evaporation efficiency, resulting in an average moisture content of 10.56%, compliant with national standards. The best medium formulation was F1 (10 g durian seed flour, 2 g sugar, 1.5 g agar, 0.25 g micronutrients, 100 mL distilled water), yielding 3.6 Ã— 10â· CFU/mL of Candida albicans colonies and an Aspergillus niger growth diameter of 28.5 mm after 72 hours of incubation. However, sporulation of Aspergillus niger was better on PDA media. Durian seed flour shows potential as an alternative fungal growth medium.